Iron restriction increases myoglobin gene and protein expression in Soleus muscle of rats - SOUZA,JANAINA S. DE (2016)
ABSTRACT Iron is an important trace element for proper cell functioning. It is present in cytochromes, hemoglobin and myoglobin (Mb), where it binds to oxygen. It is also an electron acceptor in the respiratory chain. Mb is an 18 kDa heme-protein, highly expressed in skeletal muscle and heart. The expression of several genes involved in the metabolism of iron is post-transcriptionally regulated by this element. Iron was shown to interfere with the polyadenylation step, modifying their poly (A) tail length and, as a consequence, their stability and translation rate. The aim of this study was to investigate whether iron supplementation or long and short-term restriction affects Mb gene and protein expression, as well as Mb mRNA poly(A) tail length, in cardiac and skeletal muscles of rats. Long-term iron restriction caused an increase in Mb gene and protein expression in Soleus muscle. No changes were observed in extensor digitorum longus muscle and heart. Short-term iron supplementation after iron deprivation did not alter Mb gene expression and mRNA poly(A) tail length in all tissues studied. These results indicate that Mb gene and protein expression is upregulated in response to iron deprivation, an effect that is tissue-specific and seems to occur at transcriptional level.